Wykorzystanie strategii inwestycyjnych opartych na analizie technicznej do handlu towarami z WGT SA - Górska, Anna (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2008)
The aim of the paper is to check if one was able to gain excess profits at the Warsaw Commodity Exchange. For this purpose technical analysis tools are used. Gaining excess profits would be impossible if only the market was informationally efficient. On the informationally efficient market the most effective strategy is the passive strategy “buy and hold”. If technical analysis tools permitted to gain excess profits, the weak-form efficient market hypothesis would be rejected. The analysis is carried out on the basis of the data from Warsaw Commodity Exchange in the span of 5 years: 2001–2005.